Strategi Komunikasi Pariwisata Provinsi Maluku Utara pada Event Widi International Fishing Tournamen (WIFT) 2017 - Hani Yuniani (JIKE: Jurnal Ilmu Komunikasi Efek, 2018)
Abstract Promotion of tourism that simultaneously surge in various regions in Indonesia is currently experiencing quite encouraging developments. Indonesia's tourism potential, which is largely a marine potential, encourages local governments to manage it so that it can become an icon of the region in the world arena. Sports tourism activities are now a strategy of local governments to build their region. Like the international cycling race in Ambon that encourages the acceleration of the construction of roads that become the means of competition, as well as build a connecting road to the remote areas. Today International fishing events are also the trigger of development to remote areas. This is done by North Maluku Provincial Government through the international fishing contest, Widi International Fishing Tournament 2017 (WIFT) 2017. The event held in Widi Islands, South Halmahera Regency took place on 25-29 October 2017, is expected to become a prestigious international competition for trophies president of RI. The research method used descriptive qualitative method by evaluating marketing mix principles (marketing mix). The results revealed that the preparation (planning) is the key to success of an area in organizing a sport tourism event. In communication studies, tourism promotion can be seen as practice / implementation of local government strategy in forming image / image of an organization (government). The results revealed that promotional activities and publications at the level of government conducted by Disparpor Halsel Regency has not run optimally. However, thanks to the collaboration with all stakeholders, this event can take place orderly and smoothly. This inaugural event can be quite successful. However, with all the limitations that exist, this event has proved that marine tourism Indonesia has ogled international tourists .. this is the image / image that has been successfully built properly. Keyword: Communication tourism, Marketing Mix, WIFT 2017.